2016
DOI: 10.3389/fimmu.2016.00139
|View full text |Cite
|
Sign up to set email alerts
|

The Autoimmune Ecology

Abstract: Autoimmune diseases (ADs) represent a heterogeneous group of disorders that affect specific target organs or multiple organ systems. These conditions share common immunopathogenic mechanisms (i.e., the autoimmune tautology), which explain the clinical similarities they have among them as well as their familial clustering (i.e., coaggregation). As part of the autoimmune tautology, the influence of environmental exposure on the risk of developing ADs is paramount (i.e., the autoimmune ecology). In fact, environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 261 publications
(313 reference statements)
0
56
0
2
Order By: Relevance
“…Aims to match drug target genes with disease-associated genes obtained from genetic studies. For example, the development of a monoclonal antibody inhibitor to proprotein convertase subtilizing/kexin 9 (PCSK9) following detection of a gain-of-function mutation in the gene encoding the protein in families with hypercholesterolaemia [5]. An example earlier in development is that of interferon (IFN)-a blockers, which have been developed to treat systemic lupus erythematosus (SLE), partly on the basis of genetic evidence implicating IFN signalling pathways in the aetiology [6]; a recent clinical trial has reported promising results for anifrolumab in moderate-to-severe lupus [7].…”
Section: Profile-basedmentioning
confidence: 99%
“…Aims to match drug target genes with disease-associated genes obtained from genetic studies. For example, the development of a monoclonal antibody inhibitor to proprotein convertase subtilizing/kexin 9 (PCSK9) following detection of a gain-of-function mutation in the gene encoding the protein in families with hypercholesterolaemia [5]. An example earlier in development is that of interferon (IFN)-a blockers, which have been developed to treat systemic lupus erythematosus (SLE), partly on the basis of genetic evidence implicating IFN signalling pathways in the aetiology [6]; a recent clinical trial has reported promising results for anifrolumab in moderate-to-severe lupus [7].…”
Section: Profile-basedmentioning
confidence: 99%
“…Anaya et al . ). The human as Homo microbis is an unstable and nonlinear accumulation, marked by disease tipping points with differing degrees of reversibility.…”
Section: Geography Dysbiosis and Global Healthmentioning
confidence: 97%
“…Thus, a "less is more" hypothesis could result in a limited repertoire response system towards external exposures but could be advantageous to promote stable and balanced autoimmune phenomena. The idea of the environment/exposure defining and driving a disease outcome is well accepted in autoimmunity (i.e., Autoimmune ecology) and it is starting to get the needed attention [43].…”
Section: Markermentioning
confidence: 99%